Desain Media Dadu Misteri untuk Meningkatkan Kemampuan Pemahaman Konsep IPS Subtema Manusia dan LingkunganPada Siswa Kelas V SDN Bima Kota Cirebon Tahun Pelajaran 2022/2023 - Agnes Wijayanti; Akhmad Aflaha (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine the increase in understanding of learning concepts in students with a media design approach in the form of games, as well as identify these games in increasing the ability and understanding of social studies material learning in elementary schools. This study uses the Research and Development (RnD) method. Data collection uses participant observation techniques, documentation studies, and in-depth interviews. Informants consisted of school principals, teachers, school committee, students and student guardians with a sampling technique consisting of school principals and teachers, student guardians. The data were analyzed using interpretive description techniques. The results of the research (1) make communication and interaction between teachers and students effective in the teaching and learning process. (2) to increase students' understanding of learning concepts, it is necessary to do learning with a mystery dice media design approach in the form of a game, which can be used as a source of social studies material learning and understanding of the history of the proclamation of Indonesian independence. The suggestions and recommendations of the researchers are that the mystery dice game can be used as a game-based learning resource in social studies material for grade 5 elementary schools.